Pengaruh Pemilihan Nama Merek, Pengalaman Merek, dan Ekuitas Merek terhadap Loyalitas Merek di Caffeshop Teraskita - Fifi Aley Da; Helatul Azizah; Silvia Anggraeni; Sari Wiyanti (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This research is entitled "The Influence of Brand Name Selection, Brand Experience, and Brand Equity on Brand Loyalty at Teraskita Caffeshop". The purpose of this research is to identify the extent to which brand name choice, brand experience, and brand equity influence brand loyalty among consumers. In the competitive culinary industry, brands have an important role in attracting customer attention, especially among the younger generation who pay more attention to aesthetics and brand identity. The research method used included collecting primary data through questionnaires distributed to Teraskita Caffeshop consumers. Data analysis was carried out using linear regression to determine the relationship between these variables. It is hoped that the research results will provide insight into the effectiveness of the marketing strategy implemented and recommend steps that can be taken to increase brand loyalty. It is also hoped that this research can become a reference for further research in the field of brand management.